(untitled) (KULT_online, 2010)
In his habilitaton Primavesi investigates the relation between imaginations of celebration and theatre around 1800. Borrowing from Fischer-Lichtes aesthetics of performance, ritual theories, and George Batailles theory of transgression, Primavesi sheds light on the ambivalent stance of German bourgeoisie on the idea of a non-representative celebration. The discourse on ways of creating new forms of public constantly refers to the idea of a non-representative celebration, but at the same time it is afraid of its consequences. Primavesi analyses this ambivalence within many different fields of discourse, e.g. travel literature, theatre novels, eye-witness accounts of the French Revolution, and German drama from Goethe to Büchner.